UJI AKTIVITAS ANTIBAKTERI FRAKSI KULIT BATANG NANGKA - Dira Swantara, I Made; Darmayasa, Ida Bagus Gede; Kumala Dewi, Ni Komang Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011, 2012)
This research aims to isolate and identify antibacterial compounds in jackfruit bar husk (Artocarpus heterophyllus, Lam.). 735.55 gramc of jackfruit bar husk yielded 500,25 grams of crude methanol.extract. The methanol extract was fractionated using petroleum ether, ethyl acetate and of n-butanol and then evaporated to yield crude extract of ethyl acetate 4.11 grams of petroleum ether (yellowish), 2.11 grams of ethyl acetate extract (brownish), and 1.17 grams of n-butanol (dark green). Bioactivitigs tests to Staphylococcus aureus and Eschericia coli showed that ethyl acetate extract had the largest inhibition zone. The purification of ethyl acetate extract with column chromatography resulted a faction which was antibacterial active (faction C). Identification of faction C using Gas Chromatography Mass Spectroscopy showed 3 compounds namely methyl hexadecanoate, dioctyl hexadioate, and dioctyl-1,2-benzene dicarboxylate.
Keywords: insulation, Artocarpus heterophyllus, Lam., Staphylococcus Aureus, Eschericia Coli